The Effect of Financial Ratios on Stock Prices In Food and Beverage Companies on IDX - Siregar, Oktarini Khamilah; Doriawaty, Rini (Accounting and Business Journal, 2021)
This study aims to prove the effect of Return On Equity (ROE), Dividend Payout Ratio (DPR) and Earning Per Share (EPS) on Share Prices on Food and Beverage Companies listed on the Indonesia Stock Exchange (BEI) from 2014-2018. In this study the method used is panel data regression, using the Chow Test and Hausman Test and the Fixed Effect model which is the best to use in this study. The results showed that Return On Equity (X1) had a positive and partially significant effect on Stock Prices (Y), Dividend Payout Ratio (X2) variables did not have a partially significant positive effect on Stock Prices (Y), and Earning Per Share (X3) variables a negative and significant effect partially on Stock Prices (Y). Share prices reflect the value of a company, if the company achieves good performance, then the company's shares will be much in demand by investors. The good achievements of the company can be seen from the financial statements that describe the company's financial performance.